Implementation of the Canva Media-Based Contextual Teaching and Learning (CTL) Model to Improve Arabic Vocabulary - Laily Khoirum Marzuqoh; Inayah Inayah; Waesama-ae Waemamu (South Sulawesi Education Development (SSED), 2026)
This research is based on the urgency of learning media innovation in helping students overcome challenges in mastering Arabic vocabulary. It aims to implement the Canva-based Contextual Teaching and Learning (CTL) model and measure its effectiveness in improving vocabulary mastery. The method used was quantitative, involving a pre-experimental design with a one-group pre-test and post-test, with a sample of 34 students in class X.2 (Olympic) at MAN 1 Kota Semarang. Results showed that the Canva-based CTL model was both effective and engaging, as the learning material was integrated into visualizations relevant to real-world situations. Statistically, this effectiveness was confirmed through the Wilcoxon Signed-Rank Test with a Z value of -5.090 and a significance level (Asymp. Sig. 2-tailed) below 0.001. Since the significance value < 0.05, H0 was rejected, and H1 was accepted, confirming that the Canva-based CTL model significantly improves students' Arabic vocabulary.